Վրաստանի Հանրապետության կազմավորման և ներքին քաղաքականության հիմնական սկզբունքները (1918-1921 թթ) - Մաիլյան, Բենիամին («Զանգակ - 97»)
The Georgian leaders responded to offers of German aid and on May 26, 1918, declared Georgia an independent state. All national power was delegated to a «united democratic government» to be headed by Noi Zhordania. The Georgian socialist leaders intended to introduse into Georgia certain features of the Swiss political system, such as cantonal self-rule. But, simultaneously, they supported the main idea that Georgia is a unitary country. For local authoritative bodies, the government intended to establish the institute of «erobas» (selfgovernment offices). In the second half of 1918, elections to Erobas were held. Despite the fact that almost all the seats in self-governing bodies were by the Social Democrat Labor Party of Georgia (SDLPG) members, other Georgian parties – Social Federalists (SF), National Democrats (ND) and Social Revolutionaries (SR) – had representatives in executive bodies.
Keywords: Պատմություն; Ներքին քաղաքականություն